Adaptive user selection of opportunistic multicast scheduling in wireless networks. Issue 6 (1st April 2014) - Li, Mingming; Wang, Xiaoxiang; Zhou, Jia; Qu, Jing
Abstract : In this study, an adaptive user selection of opportunistic multicast scheduling system (OMS‐AUS) scheme is proposed to improve the system throughput performance of opportunistic multicast scheduling system. Different from the previous literatures, the user selection ratio would no longer be a constant, but would vary as the number of users that have not received multicast bits changes, which can exploit the system transmission ability better. The objective is to obtain the optimal values of user selection fractions. (i) For the case without instantaneous channel state information (CSI), a channel gain distribution‐based OMS‐AUS is proposed. Firstly, a system throughput matrix (STM) is formulated to imitate the user grouping process. Secondly, the value of each element in STM is derived according to the channel gain distribution. Finally, by fully searching the elements in STM, the optimal solution is obtained. To reduce the computational complexity, a suboptimal heuristic searching scheme is also proposed. (ii) For the case with instantaneous CSI, an improved approach based on both the channel gain distribution and instantaneous CSIs is proposed. Simulation results show that both of the two proposed approaches can obtain better performance compared to the existing schemes.